Physicochemical Characterization of Sus scrofa domesticus Fat and a Preliminary Evaluation of its Potential as a Matrix Former in Ibuprofen Granules (Nigerian Journal of Pharmaceutical Research, 2020)
Background: There is an increasing interest and search for local and natural sources as active pharmaceutical excipients.Purpose: The study aimed at investigating the physicochemical characteristics of Sus scrofa domesticus (SSD) fat and its potential as a matrix former in ibuprofen granule formulations.Methods: SSD fat was extracted from the domestic pig by wet rendering and purified. The fat was characterized for its organoleptic and physicochemical properties and used in the formulation of batches of ibuprofen granules by melt granulation using varying concentrations (5.0-15%w/w). Conventional granules were formed with maize starch (15%w/w) for control. Formulated granules were evaluated for flow properties, encapsulated in hard gelatin capsules and subjected to in-vitro drug release studies.Results: SSD fat was snow white in colour. Soluble in organic solvents but insoluble in water. pH of the fat was 7.4, viscosity (147.4 millipascal), peroxide value (11.0 meq/kg), acid value (3.4) and saponification value (196.3). Granules formulated with SSD fat exhibited poor flowability and their dissolution profiles showed retardation in ibuprofen release with increase in fat concentrations. Granules formulated with 5.0 and 10%w/w of the fat exhibited 43 and 27% ibuprofen release within 4 h while the conventional granules showed a drug release of 98% within 1.0 h.Conclusion: The physicochemical properties of SSD fat was found to possess favourable potential properties relevant in the formulation of a drug delivery system. The retardation of ibuprofen release from the granules showed that SSD fat has a potential application as a matrix former in controlled release formulation.